2021
DOI: 10.1017/s0144686x21001823
|View full text |Cite
|
Sign up to set email alerts
|

Care-giver wellbeing: exploring gender, relationship-to-care-recipient and care-giving demands in the Canadian Longitudinal Study on Aging

Abstract: The three-way intersection of gender, relationship-to-care-recipient and care-giving demands has not, to our knowledge, been examined in relation to the wellbeing of family care-givers. We explore inequalities in depressive symptoms and life satisfaction, comparing wives, husbands, daughters and sons providing very-intensive care (36+ hours/week) with those providing less care and disparities between these groups in the factors related to disadvantage. Data from the Canadian Longitudinal Study on Aging (N = 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Existential issues about the current and future situation need to be raised and awareness created of their reactions to care. Previous studies highlight that caregiver responsibility poses a compelling risk since family caregivers report a lower quality of life (Chappell et al., 2021; Pinquart & Sörensen, 2011; Stefánsdóttir et al., 2022). We assume that the caregivers in our study might have the same experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existential issues about the current and future situation need to be raised and awareness created of their reactions to care. Previous studies highlight that caregiver responsibility poses a compelling risk since family caregivers report a lower quality of life (Chappell et al., 2021; Pinquart & Sörensen, 2011; Stefánsdóttir et al., 2022). We assume that the caregivers in our study might have the same experiences.…”
Section: Discussionmentioning
confidence: 99%
“…It can be overwhelming for caregivers who must balance work and family responsibilities. Studies have shown that caregiving can adversely affect caregivers' quality of life because of the weight of their responsibilities (Chappell et al., 2021; Munkejord et al., 2020; Ringer et al., 2017). The relationship between care recipients and caregivers is essential in how caregivers experience their role (Sardella et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Research [ 37 ] on informal caregivers for persons with Alzheimer's disease showed the combined influence of gender and relationship type on caregiving experience over time. A Canadian study further revealed that caregivers’ well-being is shaped by the intersection of gender, relationship type and caregiving demands [ 38 ]. It noted differences in depressive symptoms and life satisfaction among spousal caregivers, sons and daughters, based on the intensity of their caregiving.…”
Section: Introductionmentioning
confidence: 99%